Evolution of smart grids towards the Internet of energy: Concept and essential components for deep decarbonisation. Issue 1 (20th November 2022) - Ghiasi, Mohammad; Wang, Zhanle; Mehrandezh, Mehran; Jalilian, Shayan; Ghadimi, Noradin
Abstract: To achieve low‐carbon sustainable energy development, new technologies such as Internet of Energy (IoE), intelligent systems and Internet of Things (IoT) as well as distributed energy generations via smart grids (SG) are gaining attention. The interoperability between intelligent energy systems, realised through the web, enables automatic consumption optimisation and increases network efficiency and intelligent management. IoE is an intriguing topic in close connection with the IoT, communication systems, SG and electrical mobility that contributes to energy efficiency to achieve zero‐carbon technologies and green environments. Furthermore, nowadays, the widespread growth and utilisation of processors for mining digital currency in homes and small warehouses are some other factors to be considered in terms of electric energy consumption and greenhouse gas emission. However, research on the use of the Internet for evaluating the misallocation of energy and the effect it can have on CO2 emissions is often neglected. In this study, the authors present a detailed overview regarding the evolution of SG in conjunction with the employment of IoE systems as well as the essential components of IoE for decarbonisation. Also, mathematical models with simulation are provided to evaluate the role of IoE in reducing CO2 emission. Abstract : In this study, we present a detailed overview regarding the evolution of smart grids towards modern Internet energy systems. We present the essential components of Internet of Energy (IoE) for decarbonisation in the future of energy sector. Also, some models and equations are provided to evaluate the effects of IoE and the misallocation of energy on CO2 in different regions.